Fostering Writing Skills Through Self-Learning Materials (2021)
ABSTRACT: The Covid 19 pandemic, and the subsequent confinement of the population forced teachers to seek alternatives to continue the learning process of students. This paper reports an action research experience with seventh graders at Institución Educativa Fundadores in Medellín where Self-Learning Materials with a Product-Based Writing approach were implemented with the aim of fostering the students’ writing skills. The data collection instruments used were students’ artifacts, an interview with the Cooperating Teacher, and a survey for students. The analysis was made through the triangulation of the sources and the results evidenced that the characteristics of the Self-Learning Materials combined with the Product-Based approach had a positive effect on the students’ writing skills in most of the categories assessed.